Lactococcus garvieae Isolates from Rainbow Trout (Oncorhynchus mykiss, W.) Compared by PLG and SA1B10 PCR Primer Pairs - Altan, ErbÃ¼lent; Korun, Jale (Sam Ratulangi University, 2021)
The aim of this study was to identify and compare Lactococcus garvieae strains using the PLG primer pair and SA1B10 primer pair. Also, the antibiotic resistance of the strains was investigated in the study. For this aim, commercial trout farms at Kemer, Korkuteli, and Manavgat, Antalya Province, Turkey were visited every month from June to September 2018. Thirty sick fish were sampled in the study. Lethargy, anorexia, darkening of skin color, unilateral or bilateral exophthalmos, opacification and hemorrhages in the eyes of the sick fish, and abdominal dropsy were observed. At necropsy, hemorrhages in the internal organs, splenomegaly, and darkening of the spleen and ascites were present. Seventy-five strains from sick fish samples verified on the basis of the biochemical characterization and PCR studies. The strains showed homogeneity in terms of phenotypic characteristics and all strains were identified as Lactococcus garvieae. The PCR technique was applied to 50 of 75 strains using PLG primer pair. While 47 of 50 strains gave positive results, amplification was not observed in 3 strains. When the PCR technique using SA1B10 primer pair was applied to a total of 25 strains, 3 of which were negative, 22 of which gave positive amplification, and 25 strains gave positive results. Resistance was determined by the disk diffusion method. All seventy-five strains were resistant to ampicillin and all strains were susceptible to bacitracin and tetracycline. It was found that the resistance and susceptibility of the strains showed variation to other antibiotics used in the study.Keywords: Lactococcus garvieae; Rainbow Trout; PCR; Antibiotic